The coupled atom transistor. (18th March 2015) - Jehl, X; Voisin, B; Roche, B; Dupont-Ferrier, E; De Franceschi, S; Sanquer, M; Cobian, M; Niquet, Y-M; Sklénard, B; Cueto, O; Wacquez, R; Vinet, M
Abstract: We describe the first implementation of a coupled atom transistor where two shallow donors (P or As) are implanted in a nanoscale silicon nanowire and their electronic levels are controlled with three gate voltages. Transport spectroscopy through these donors placed in series is performed both at zero and microwave frequencies. The coherence of the charge transfer between the two donors is probed by Landau–Zener–Stückelberg interferometry. Single-charge transfer at zero bias (electron pumping) has been performed and the crossover between the adiabatic and non-adiabatic regimes is studied.